Psikoanalisis Sigmund Freud Dalam Memahami Konflik Tokoh Utama Novel “Maryam” Karya Okky Madasari - Ayu Lestari; Hana Ghina Hanifah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is motivated by the researcher’s curiosity about discrimination and social conflict, which are the central themes in the novel Maryam by Okky Madasari. The main character in this novel, Maryam, faces an inner conflict between maintaining her personal beliefs and coping with the social pressures exerted by her community and family. The internal and external conflicts experienced by Maryam illustrate the psychological dynamics of individuals living in an intolerant environment. To understand these conflicts, this study applies Sigmund Freud's psychological approach, emphasizing the interaction among the id, ego, and superego. The method used in this research is descriptive qualitative, employing a literature review. The analysis reveals that while Maryam’s id drives her to uphold her freedom and personal beliefs, her superego imposes pressure through societal norms and family expectations. Meanwhile, Maryam's ego functions as a mediator, seeking a compromise, though this leads to emotional distress. These internal and external conflicts reflect the social realities faced by individuals from minority groups, which can significantly influence their life choices.